Monitoring Insecticide Resistance Profiles of Aedes aegypti (Diptera: Culicidae) in the Sunda Islands of Indonesia Based on Diagnostic Doses of Larvicides. Issue 2 (20th November 2018) - Haziqah-Rashid, A; Chen, C D; Lau, K W; Low, V L; Sofian-Azirun, M; Suana, I W; Harmonis, H; Syahputra, E; Razak, A; Chin, A C; Azidah, A A
Abstract: This study was conducted to monitor the susceptibility status of Aedes aegypti (Linnaeus) larvae in the Sunda Islands of Indonesia against various organophosphates and organochlorines. Larval bioassay was performed in accordance with the World Health Organization standard protocol. Field-collected and reference strains of Ae. aegypti larvae were tested against diagnostic doses of eight larvicides belonging to organophosphates and organochlorines, namely bromophos (0.050 mg/liter), chlopyrifos (0.002 mg/liter), fenitrothion (0.020 mg/liter), fenthion (0.025 mg/liter), malathion (0.125 mg/liter), temephos (0.012 mg/liter), DDT (0.012 mg/liter), and dieldrin (0.025 mg/liter). Mortality rates of larvae were recorded at 24-h posttreatment. This study showed that Ae. aegypti larvae from Padang, Samarinda, Manggarai Barat, and South Central Timor were susceptible to both fenitrothion and dieldrin (mortality rates ≥ 98%). About 6 out of 10 field strains of Ae. aegypti larvae were resistant (<80% mortality rates) against fenthion, whereas Ae. aegypti larvae from Kuningan, Samarinda, Sumba, and South Central Timor exhibited some degrees of resistance (mortality rates 80–98%). All field-collected Ae. aegypti larvae were resistant against diagnostic doses of chlorpyrifos, malathion, temephos, and DDT with mortality rates ranging from 0 to 74.67%. Continued insecticide susceptibility studies are essential to identify the efficacy of insecticides for an improved dengue vector control and to delay the development of insecticide resistance.